Birds in the Head. Dialogues between Didactics and Visual Arts (Praxis Educativa, 2026)
Throughout history, the relations between didactics and the visual arts have navigated diverse approaches, proposals, encounters, and misunderstandings. Today, the massive emergence of generative artificial intelligence compels us to revise assumptions and practices. Images circulating in educational spaces arise from statistical probabilities that homogenize anomalies and singularities. These are mean images that, in their infinite multiplication, dull interest and fatigue the gaze. Within this scenario, this article addresses the articulations between didactics and the visual arts based on three experiences in university teacher training: 1) “Image against image”, the collective construction of alternative repertoires to spam images; 2) “Intervene, act, create”, the situated image as a political act; and 3) “The optical unconscious and Grete Stern’s Dreams”, routines of vision, photographic creation, feminisms, and identity.
Keywords: mean image; situated teachings; didactic sensorium; intervention; poetic didactics